Factors Affecting the Incidence of Uncontrolled Hypertension in Patients Performing Routine Examinations at the Kebayakan Public Health Center, Central Aceh Regency - Nadapdap, Thomson P.; Nasution, Zuraidah; Wahyudi, Indra (International Journal Papier Advance and Scientific Review, 2021)
The purpose of the study was to determine the factors that influence the incidence of uncontrolled hypertension in patients who carry out routine checks at the Community Health Center (Puskesmas). Method: using analytical survey method using Case Control research design. The sample was 148 respondents, 74 case groups and 74 control groups were taken by purposive sampling. Data analysis was performed univariate, bivariate and multivariate with multiple logistic regression. The results of the bivariate test showed that the factors influencing the incidence of uncontrolled hypertension were age (p= 0.002; OR = 3,253), family history (p= 0.000; OR = 4.216), obesity (p= 0.005; OR = 2.734), physical activity (p= 0.000; OR = 4.229), salt consumption (p= 0.000; OR = 4,127), coffee consumption (p= 0.010; OR = 4,127), stress (p= 0.000; OR = 3,745), medication adherence (p= 0.000; OR = 4.492). Factors that were not related were gender (p= 0.620; OR = 0.803), smoking (p= 1,000; OR = 1,000). While the results of the multivariate test showed that the most influential factors with the incidence of uncontrolled hypertension were medication adherence variable (p= 0.000; Exp(B) = 5.982), and obesity variable (p= 0.002; Exp(B) = 4.945). In conclusion, the dominant factors that influence the incidence of uncontrolled hypertension at the Kebayakan Health Center are medication adherence and obesity.